2021
DOI: 10.3390/ijerph181910092
|View full text |Cite
|
Sign up to set email alerts
|

Mental Health during COVID-19 Pandemic among Caregivers of Young Children in Kenya’s Urban Informal Settlements. A Cross-Sectional Telephone Survey

Abstract: The emergence of COVID-19 has profoundly affected mental health, especially among highly vulnerable populations. This study describes mental health issues among caregivers of young children and pregnant women in three urban informal settlements in Kenya during the first pandemic year, and factors associated with poor mental health. A cross-sectional telephone survey was administered to 845 participants. Survey instruments included the Patient Health Questionnaire-9, General Anxiety Disorder-7 scale, COVID-19 A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
38
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 44 publications
1
38
0
6
Order By: Relevance
“…Our findings support new evidence from other LMICs on the state of mental health during the pandemic. For instance, a recent study conducted in a socially and economically comparable setting in Kenya, reported elevated rates of depression (34.1%) and GAD (14.0%) [2] while in Bangladesh, the estimated prevalence of depression was 33.0% [25]. A further study from the United Kingdom [26] has compared pre-and post-COVID-19 rates of psychological distress and has shown that deterioration of mental health did not recover after COVID-19 restrictions were eased.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Our findings support new evidence from other LMICs on the state of mental health during the pandemic. For instance, a recent study conducted in a socially and economically comparable setting in Kenya, reported elevated rates of depression (34.1%) and GAD (14.0%) [2] while in Bangladesh, the estimated prevalence of depression was 33.0% [25]. A further study from the United Kingdom [26] has compared pre-and post-COVID-19 rates of psychological distress and has shown that deterioration of mental health did not recover after COVID-19 restrictions were eased.…”
Section: Discussionmentioning
confidence: 99%
“…The uncertainties and unpredictable nature of the pandemic resulted in individuals experiencing various forms of mental health problems such as depression, anxiety, psychosocial dysfunction, dissociation disorders, substance abuse, and insomnia. It was projected that these effects would be most severe in lowresourced settings due to constraints related to weak health systems with limited access to mental health services [2]. Low-resourced settings such as slum residences comprise of informal dwelling units which are poorly constructed, crowded with poor sanitary conditions and environmental pollution [3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In China [18], reported that women endorsed higher levels of hyperarousal, difficulty sleeping, and negative reactions or moods, symptoms commonly associated with posttraumatic stress disorder. Several studies proposed that the disproportionate number of women experiencing "high stress" is potentially attributable to women being more likely to work in high-risk environments, such as clinics, or as a function of their status as primary caregivers to children, significant others, or parental figures [19][20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%
“…In this Special Issue, entitled “Mental health in the time of COVID-19”, several studies, carried out in different parts of the world, such as China [ 66 ], Canada [ 67 ], the UK [ 68 ], Greece [ 69 ], Poland [ 70 ], Norway [ 71 ], India [ 72 ], Mexico [ 73 ], Malaysia [ 74 ], Kenya [ 75 ], Saudi Arabia [ 76 ], and Switzerland [ 77 ], describe the impact of the pandemic on different dimensions of people’s mental health.…”
mentioning
confidence: 99%